Eternity & Oranges - Bakken, Christopher, 1967- (Pitt poetry series., 2016)
"We'd not slept in days, or else we were/ still sleeping--who could tell?" someone asks in the opening poem of Eternity & Oranges. The voices we encounter in this book speak on the verge of disappearance, from places marked by disintegration and terror. Christopher Bakken's poems are acts of conjuring. They move from the real political landscapes of Greece, Italy, and Romania, into more surreal spaces where history comes alive and the summoned dead speak. In the formally diverse long poem, "Kouros/Kore," but also in this book's terse and harrowing dream songs, Bakken writes with devastating force, at every turn "Guilty of the crime of praise" while "begging for an antidote to beauty."